Caliphate and kingship in a fifteenth-century literary history of Muslim leadership and pilgrimage : a critical edition, annotated translation, and study of al-D̲ahab al-Masbūk fī d̲ikr man ḥaǧǧa min al-ḫulafā' wa-l-mulūk - Steenbergen, J. van. (Bibliotheca Maqriziana, 2017)
In Caliphate and Kingship in a Fifteenth-Century Literary History of Muslim Leadership and Pilgrimage Jo Van Steenbergen presents a new study, edition and translation of al-Ḏahab al-Masbūk fī Ḏikr man Ḥağğa min al-Ḫulafāʾ wa-l-Mulūk , a summary history of the Muslim pilgrimage to Mecca by al-Maqrīzī (766-845 AH/ca. 1365-1442 CE). Traditionally considered as a useful source for the history of the ḥağğ , al-Ḏahab al-Masbūk is re-interpreted here as a complex literary construction that was endowed with different meanings. Through detailed contextualist, narratological, semiotic and codicological analyses Van Steenbergen demonstrates how these meanings were deeply embedded in early-fifteenth century Egyptian transformations, how they changed substantially over time, and how they included particular claims about authorship and about legitimate and good Muslim rule.